2022
DOI: 10.1302/2046-3758.119.bjr-2022-0078.r1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing periprosthetic joint infections

Abstract: Aims This study evaluated the definitions developed by the European Bone and Joint Infection Society (EBJIS) 2021, the International Consensus Meeting (ICM) 2018, and the Infectious Diseases Society of America (IDSA) 2013, for the diagnosis of periprosthetic joint infection (PJI). Methods In this single-centre, retrospective analysis of prospectively collected data, patients with an indicated revision surgery after a total hip or knee arthroplasty were included between 2015 and 2020. A standardized diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 33 publications
0
21
0
2
Order By: Relevance
“…15 Therefore, to date, there is no gold standard for diagnosing RA-PJI. 16 However, if the preoperative diagnostic process does not provide sufficient information for a definite diagnosis, it can affect treatment decisions. [17][18][19][20] Many studies have confirmed the limited diagnostic efficiency of CRP, ESR, synovial fluid WBC, or PMN% alone; additionally, because the above indexes are usually not specific for diagnosing RA-PJI, previous studies have not typically analyzed their diagnostic value in this context.…”
Section: Discussionmentioning
confidence: 99%
“…15 Therefore, to date, there is no gold standard for diagnosing RA-PJI. 16 However, if the preoperative diagnostic process does not provide sufficient information for a definite diagnosis, it can affect treatment decisions. [17][18][19][20] Many studies have confirmed the limited diagnostic efficiency of CRP, ESR, synovial fluid WBC, or PMN% alone; additionally, because the above indexes are usually not specific for diagnosing RA-PJI, previous studies have not typically analyzed their diagnostic value in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The ICM 2018 criteria miss low-grade infections to a certain extent; 32 however, other criteria, such as those of the EBJIS can over-diagnose PJI. 33 As an additional limitation, at our hospital, the standard procedure is to incubate cultures for 14 days, as in several other hospitals. 9,24,29 Incubation periods for lowvirulence organisms can require additional time and may result in negative cultures if evaluated too soon.…”
Section: Discussionmentioning
confidence: 99%
“…The ICM 2018 criteria miss low-grade infections to a certain extent; 32 however, other criteria, such as those of the EBJIS can over-diagnose PJI. 33…”
Section: Discussionmentioning
confidence: 99%
“…Minor criteria involve (1) elevated C‐reactive protein and erythrocyte sedimentation rate, (2) elevated synovial fluid white blood cell count or positive change on leukocyte esterase test strip, (3) elevated synovial fluid polymorphonuclear neutrophil percentage, (4) positive histological analysis of periprosthetic tissue, and (5) a single positive culture [14]. Though newer PJI definition criteria exist that may be more sensitive for diagnosis [15], the diagnostic information from patients involved in this study better aligned with the 2013 MSIS criteria. This criterion also provided a more concrete outcome of PJI positive or negative, which was desired in the current study for simplicity when comparing to ISC and clinical microbiology.…”
Section: Methodsmentioning
confidence: 99%